2018
DOI: 10.3892/ijo.2018.4561
|View full text |Cite
|
Sign up to set email alerts
|

Novel SIRT1 inhibitor 15-deoxy-Δ12,14-prostaglandin J2 and its derivatives exhibit anticancer activity through apoptotic or autophagic cell death pathways in SKOV3 cells

Abstract: Clinically relevant sirtuin (SIRT) inhibitors may possess antitumor activities. A previous study indicated that 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) exhibited potent anticancer activity by SIRT1 inhibition. Therefore, the aim of the present study was to investigate whether its derivatives (J11-C1 and J19) exhibited anticancer activity against ovarian cancer SKOV3 cells. Cell viability was determined using an MTT assay. Cell cycle arrest, apoptosis and autophagy were determined using flow cytometry or we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…This is in accordance with findings of Lara and coworkers [47], who showed that SIRT1inhibitors can induce massive apoptosis in p53-dependentcancers, but not in p53-independent cells. Our previous study showed the strongest induction of apoptosis in MCF-7 cells after treatment with salermide, a SIRT1 inhibitor, but SKOV3 cells showed only about a 10% increase in apoptosis [45,[48][49][50]. It appears that this observation in MCF-7 cells was due to the presence of the wild-type p53, since p53-deficient SKOV3 cells show only a small increase in apoptosis due to salermide [51].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with findings of Lara and coworkers [47], who showed that SIRT1inhibitors can induce massive apoptosis in p53-dependentcancers, but not in p53-independent cells. Our previous study showed the strongest induction of apoptosis in MCF-7 cells after treatment with salermide, a SIRT1 inhibitor, but SKOV3 cells showed only about a 10% increase in apoptosis [45,[48][49][50]. It appears that this observation in MCF-7 cells was due to the presence of the wild-type p53, since p53-deficient SKOV3 cells show only a small increase in apoptosis due to salermide [51].…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, overexpression of SIRT1 increased the chemotherapy resistance in IGROV1 cells and knock-down of SIRT1 led to cell growth arrest and enhanced the sensitivity of drug-resistant cells to DOX [44]. Therefore, inhibition of SIRT1 resulted in anticancer effects in SKOV3 cells through apoptotic or autophagic cell death pathways [45]. SIRT1 enhanced cell proliferation, chemo-resistance and aggressiveness by up-regulating multiple antioxidant pathways to inhibit oxidative stress [46].…”
Section: Discussionmentioning
confidence: 99%
“…Plant secondary metabolites are a diverse range of biologically active molecules having multiple pharmacological actions like antimicrobial, stimulant, analgesic, anthelmintic, anticoagulant, antiacne, and antioxidant, among others (Debnath et al, 2012;Bhakta, 2012, 2013;Dey et al, 2012bDey et al, , 2014Karuna et al, 2018aKaruna et al, , 2018bKundu et al, 2019). Different synthetic compounds show potential biological activity in vitro as well as in vivo ( Jeon et al, 2017;Jeong et al, 2017a, b;Kim et al, 2018;Lee et al, 2018Lee et al, , 2019Richa et al, 2019;Tae et al, 2018), and various formulations of existing drugs are also developed to increase the safety profile (Gorain et al, 2014;Karmakar et al, 2015;Maity et al, 2016). In spite of this technological development, humans from almost every culture are efficiently employing the plant-derived compounds for the anticipation and management of multiple health disorders for many centuries (Dey et al, 2012a, c).…”
Section: The Biological Activity Of Alkaloidsmentioning
confidence: 99%
“…Inhibition of SIRT1 in endometric cancer cells (Ishikawa) or LumA (MCF-7) cells using MHY2256 also increased apoptosis and accumulated LC3B-II and eventually BECLIN-1, ATG5, ATG7, and autophagy vesicles [79,80]. Treatment of ovarian cancer cells (SKVO3) with different derivatives of a SIRT1 family inhibitors (J11-C1, 15dPGJ2, J19, or MHY2256) affected cell survival and also increased autophagy marker expression (LC3B-II, and/or BECLIN-1, and ATG13), whereas inhibition of autophagy using 3-MA strongly reduced cell death [78,80].…”
Section: Ambivalent Role Of the Sirt Family (Class Iii) In Autophagy mentioning
confidence: 99%